Yasmin in charge - Faruqi, Saadia; Aly, Hatem (Picture Window Books, a Capstone imprint, 2019)
"In this collection of four stories, Yasmin takes charge of some sticky situations! At home, at school, or out and about, Yasmin faces challenges head on with creativity and quick thinking. Whether she's creating a new recipe, finding a way to rescue a stuck toy for a little friend, or calming down monkeys (and classmates!), a clever solution to any problem is just around the corner!"--Amazon.com.
Yasmin the teacher -- Yasmin the chef -- Yasmin the zookeeper -- Yasmin the superhero.
Keywords: Muslim girls -- Juvenile fiction; Pakistani Americans -- Juvenile fiction; Muslim families -- Juvenile fiction; Problem solving -- Juvenile fiction